Influence of Polyphenol Levels on the Perception of Aroma in Vitis vinifera cv. Malbec wine - Goldner, M.C.; di Leo Lira, P.; van Baren, C.; Bandoni, A. (South African Journal of Enology and Viticulture, 2016)
The aim of this study was to explore the effect of two ranges of polyphenols naturally present in Malbec wine, high concentrations (4.5-7.2 g/L) and low (1.4-3.2 g/L), on the perception of aroma. Samples with a maximum ethanol level of 13.5% were taken from the fermentation tanks before the clarification and filtration process. A Quantitative Descriptive Analysis of wines was assessed by ten trained assessors, and HS-SPME-GC-MS and physicochemical analyses were performed. The intensities of fruity (P < 0.01), citrus (P < 0.01), strawberry (P < 0.05), cooked fruit (P < 0.01) and floral (P < 0.01) aromas decreased when the level of polyphenols increased. Neither volatile compounds nor physicochemical analyses were significant in the two groups of wines.